Impact of Pollution on Animal Products
DOI: 10.1007/978-1-4020-8359-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals and Trace Elements Content in Camel Milk and Shubat from Kazakhstan

Abstract: In Kazakhstan, camel milk is mainly consumed after fermentation process. The fermented camel milk, named shubat, is generally home-made by the traditional process. The changes in mineral composition of camel milk during the fermentation process were rarely studied especially for heavy metals. The present study aimed to assess the change in heavy metals and trace-elements contents during the fermentation process.Samples of milk and shubat were collected in eight farms of Southern Kazakhstan in order to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
2
2

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
9
2
2
Order By: Relevance
“…[21] reported that the overall mean of Pb and Cd contents in camel milk in Egypt were 1056±105.85 and 8.00±0.21 ppb, respectively. The obtained results agreed with those reported by Saini et al(2007) [22], Meldebekova et al (2008)[23] and El-Bagermi et al (2014)[24]. To the best of our knowledge, there were no previously published data on detection of Hg in camel milk samples.…”
supporting
confidence: 92%
“…[21] reported that the overall mean of Pb and Cd contents in camel milk in Egypt were 1056±105.85 and 8.00±0.21 ppb, respectively. The obtained results agreed with those reported by Saini et al(2007) [22], Meldebekova et al (2008)[23] and El-Bagermi et al (2014)[24]. To the best of our knowledge, there were no previously published data on detection of Hg in camel milk samples.…”
supporting
confidence: 92%
“…Similar trend was observed of zinc concentration in booth milk (Table 2). The present result is closed to that reported by Meldebekova et al (2008) and El-Bagermi et al (2014), who found that the concentration of copper in camel milk was 0.065±0.04 and 0.08 ± 0.05 mg/l, respectively. Similar trend was reported by Alwan et al (2014), who found that concentration of copper and zinc in Farm-reared and Desert-reared Libyan Maghrebi Camels' Milk was 0.58±0.052, 0.24±0.27 and 0.42 ±0.02, 0.14±0.02 mg/kg, respectively.…”
Section: Concentrations Of Copper and Zinc In Pasture And Farms Camelcontrasting
confidence: 68%
“…Camel milk is used in hot and arid regions as an essential nutritional source, for high energy and vitamins contents (Gorakh et al, 2000 andAl-Awadi andSrikumar, 2001). Camel milk, use as medicinal, dietary properties and used as a fresh milk in some countries (Faye et al, 2008 andMeldebekova et al, 2008). These properties are widely exploited for human health (Kenzhebulat et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lead content in milk was positively correlated to the traffic density, (from 0.36 ppm on average for a traffic density of 10 vehicles per day to 7.20 ppm on average for a traffic density of 15000 vehicles per day) [9]. Lead concentration in cow milk was on average of 0.00132 ppm in rural area and of 0.25 ppm in industrial area and 0.032 ppm close a road [10][11][12]. In Germany and Holland, higher value allowed is 0.05 ppm of Pb in milk; 0.02 ppm in Turkey and 0.1 ppm in Kazakhstan.…”
Section: Discussionmentioning
confidence: 99%